2002
DOI: 10.1089/104303402760372909
|View full text |Cite
|
Sign up to set email alerts
|

A Human Immunodeficiency Virus Type 1polGene-Derived Sequence (cPPT/CTS) Increases the Efficiency of Transduction of Human Nondividing Monocytes and T Lymphocytes by Lentiviral Vectors

Abstract: We have investigated the capacity of two human immunodeficiency virus type 1-derived lentivectors, differing in the presence of a 118-bp pol fragment containing the cPPT/CTS element, to transduce human normal primary cells of different hematopoietic lineages. Infection of resting monocytes with a high multiplicity of infection (MOI > 10) revealed that the lentivirus carrying the pol fragment (cPPT) is effective, transducing 75% of cells compared with 36% for the no-cPPT vector. Even at low MOIs (< or =1) the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
40
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 65 publications
(49 reference statements)
3
40
0
Order By: Relevance
“…Previous studies have shown that the incorporation of a central polypurine tract (cPPT) 16 and woodchuck hepatitis virus post-transcriptional regulatory element (WPRE) 17 can increase transgene expression levels. By incorporating these elements into the lentiviral backbone (Fig.…”
Section: Lentiviral Infection Of Human Stem Cellsmentioning
confidence: 99%
“…Previous studies have shown that the incorporation of a central polypurine tract (cPPT) 16 and woodchuck hepatitis virus post-transcriptional regulatory element (WPRE) 17 can increase transgene expression levels. By incorporating these elements into the lentiviral backbone (Fig.…”
Section: Lentiviral Infection Of Human Stem Cellsmentioning
confidence: 99%
“…In To construct the lentiviral vectors (CS-env-shRNA, CS-m-env-shRNA), the generated U6 hairpin vectors were digested with EcoR I and Nhe I and then cloned into the same site in the lentiviral transfer vector (CS-CDF-CG-PRE) (Naldini et al, 1996;Manganini et al, 2002;Rubinson et al, 2003;Stewart et al, 2003). …”
Section: Hiv-1 Infection Is a Worldwide Disease That Requires Alternamentioning
confidence: 99%
“…For the control vector, a G was mutated to a C in the siRNA sequence. We also constructed two different strand vectors, antisense (env-A) and sense (env-S), which were under the control of the U6 promoter (Figure 1) (Naldini et al, 1996;Manganini et al, 2002;Rubinson et al, 2003;Stewart et al, 2003), to generate the CS-env-shRNA and control transfer vectors (CS-m-envshRNA). The sequences and orientations of the constructed vector inserts were confirmed by nucleotide sequencing.…”
Section: Reverse Transcription-pcr (Rt-pcr) Analysismentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19][20][21][22][23] Viral vector particles were generated by cotransfection of the VSV containing plasmid pMD-G, the packaging construct pCMVdR8.74 and the indicated transfer constructs into 293T cells, followed by determination of concentration of particles by ultracentrifugation, as previously described. 65 Viral titers were evaluated by infecting a known number of REH cells with different volumes of viral vector preparations in a 200 ml volume. 65,66 B-cell precursor ALL cells were collected from 14 children at diagnosis, purified using Ficoll-HyPaque (Pharmacia LKB, Uppsala, Sweden) and frozen until use.…”
mentioning
confidence: 99%
“…65 Viral titers were evaluated by infecting a known number of REH cells with different volumes of viral vector preparations in a 200 ml volume. 65,66 B-cell precursor ALL cells were collected from 14 children at diagnosis, purified using Ficoll-HyPaque (Pharmacia LKB, Uppsala, Sweden) and frozen until use. In all cases, more than 80% of blast infiltration was present and more than 90% of the blasts expressed CD19 antigen and lacked surface Ig (sIg).…”
mentioning
confidence: 99%